Factors Associated with Preventive Practices of Type 2 Diabetes Mellitus - Nissa Kusariana; Tutut Okta Hardiyanti; Moh. Arie Wurjanto (Universitas Airlangga, 2021)
Background: Diabetes mellitus is a non-communicable disease that can be prevented by controlling the risk factors. Diabetes mellitus prevention practice is important so that prevention of type 2 diabetes mellitus can be carried out effectively. There are several factors that cause a person to practice prevention against diabetes mellitus. Objective: This study aims to analyze factors related to the practice of type 2 diabetes mellitus prevention among Diponegoro University students in Semarang. Methods: This is a quantitative study with an observational analytic approach and a cross-sectional study design. The time of research was May-August 2020. The instrument in this study was a google form questionnaire. The population in this study were active undergraduate students of Diponegoro University in 2020, amounting to 36,425 students. The sample size in this study was 407 respondents. The variables of the study were family history of type 2 diabetes mellitus, knowledge level, attitude, family support, and preventive practices of type 2 diabetes mellitus. This study used univariate analysis and bivariate analysis. The relationship test was performed using the chi-square test on a computer application. Results: This study showed there was a significant relationship between family history type 2 diabetes mellitus (0,017), knowledge level (0,00), attitude (0,00), and family support (0,00) for the preventive practices of type 2 diabetes mellitus in students. Conclusion: Family history of type 2 diabetes mellitus, knowledge level, attitude, and family support are factors related to the preventive practices of type 2 diabetes mellitus among students of Diponegoro University in Semarang. There is a need for education and provision of information related to knowledge on diabetes mellitus prevention for students at Diponegoro University, Semarang.